2020
DOI: 10.3390/cancers12061546
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Escalation Is Crucial in Anti-CTLA-4 Antibody Therapy to Enhance Local and Distant Antitumor Effect in Murine Osteosarcoma

Abstract: We previously reported that a combination of 10 Gy of X-ray irradiation and dual immune checkpoint blockade with anti-CTLA-4 (C4) and anti-PD-L1 antibodies produced a significant shrinkage of irradiated and unirradiated tumors (abscopal effect) and prolonged overall survival. However, the optimal radiation delivery regimen combined with single immune checkpoint blockade of C4 for inducing a maximum systemic antitumor response still remains unclear, particularly for patients with osteosarcoma. We used syngeneic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…Importantly, Tregs surviving 10 Gy irradiation had a weakened ability to suppress CD8 + T-cells. Similarly, Takenaka et al reported that a single dose of 10 Gy X-rays, or 24 Gy delivered in three fractions, reduced Treg numbers in tumor tissue in a tumor transplant mouse model (28). These studies suggest that our results may be due to a reduction of CTLA-4 expressing Tregs in response to X-rays.…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, Tregs surviving 10 Gy irradiation had a weakened ability to suppress CD8 + T-cells. Similarly, Takenaka et al reported that a single dose of 10 Gy X-rays, or 24 Gy delivered in three fractions, reduced Treg numbers in tumor tissue in a tumor transplant mouse model (28). These studies suggest that our results may be due to a reduction of CTLA-4 expressing Tregs in response to X-rays.…”
Section: Discussionsupporting
confidence: 75%
“…Using the same OS mouse model, Takenada and colleagues showed that the combination of high-dose local radiation and anti-CTLA4 antibody administration is able to halt tumor growth not only of the treated lesion, but also of a contralateral, untreated tumor (abscopal effect). Also in this work, treatment was able to severely reduce the number of FOXP3 + Tregs in both treated and untreated lesion [ 42 ]. Another T cell sub-population that has been implicated in tumor progression, although with controversial data, is the T helper 17 (Th17) subset [ 43 ].…”
Section: The Heterogenous Bone Marrow Microenvironmentmentioning
confidence: 95%
“…Further analysis revealed that both P1+pre-Rad and P1+conc-Rad regimens successfully suppressed tumor growth not only in local, but also distant tumors. However, only 2 (15%) and 1 (5.9%) mice in P1+pre-Rad and P1+conc-Rad groups, respectively, survived for more than 50 days after the initial treatment, whereas our previous studies demonstrated that 3 of 7 (42.9%) mice in P1C4 with radiation therapy at 10 Gy [ 20 ] and more than 30% in C4 with radiation at 16 Gy or 8 Gy × 3 fraction groups [ 39 ] survived for more than 50 days after the initial treatment. Therefore, further improvement in therapeutic efficacies may be achieved by using escalated dose to a local tumor.…”
Section: Discussionmentioning
confidence: 99%